2017
DOI: 10.1371/journal.pone.0190380
|View full text |Cite
|
Sign up to set email alerts
|

ESBL-producing Escherichia coli in Swedish gulls—A case of environmental pollution from humans?

Abstract: ESBL-producing bacteria are present in wildlife and the environment might serve as a resistance reservoir. Wild gulls have been described as frequent carriers of ESBL-producing E. coli strains with genotypic characteristics similar to strains found in humans. Therefore, potential dissemination of antibiotic resistance genes and bacteria between the human population and wildlife need to be further investigated. Occurrence and characterization of ESBL-producing E. coli in Swedish wild gulls were assessed and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 47 publications
4
63
0
Order By: Relevance
“…Our study revealed frequent occurrence of carbapenemase- and ESBL-producing Enterobacteriaceae (16% and 55%, respectively) colonizing gulls from the Lisbon coastline, Portugal. ESBL-producing Enterobacteriaceae among gulls were previously reported in USA [ 6 ], Canada [ 4 ], Chile [ 5 ], and in different countries in Europe [ 8 , 31 , 32 , 33 , 34 ], including Portugal in 2008 [ 12 , 13 ]. The high heterogeneity observed here in terms of bacterial species, ST, and resistance determinants showed that the high resistance rates observed were basically not simply consequences of shared microbiota between bird individuals, that could have biased our observation.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed frequent occurrence of carbapenemase- and ESBL-producing Enterobacteriaceae (16% and 55%, respectively) colonizing gulls from the Lisbon coastline, Portugal. ESBL-producing Enterobacteriaceae among gulls were previously reported in USA [ 6 ], Canada [ 4 ], Chile [ 5 ], and in different countries in Europe [ 8 , 31 , 32 , 33 , 34 ], including Portugal in 2008 [ 12 , 13 ]. The high heterogeneity observed here in terms of bacterial species, ST, and resistance determinants showed that the high resistance rates observed were basically not simply consequences of shared microbiota between bird individuals, that could have biased our observation.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, five different STs were detected among the ESBL E. coli (Table ). The majority of these, including ST58, ST205, ST540, and ST1722, have already been reported in ESBL‐producing E. coli from waterfowl in Pakistan (Mohsin et al., ), gulls in Chile (Hernandez et al., ) Portugal (Guenther et al., ) and Sweden (Atterby et al., ). Interestingly, E. coli ST1193 belongs to extraintestinal pathogenic pandemic clonal group associated with urinary tract infections (UTIs) in humans and is, similar to the E. coli ST131 H30 clone, an important contributor to fluoroquinolone resistance worldwide (Tchesnokova et al., ).…”
Section: Antimicrobial Resistant Escherichia Coli Obtained By Nonselementioning
confidence: 94%
“…Some of the main anthropogenic sources of the AMR bacteria in wildlife already suggested were landfills, insufficiently treated wastewaters draining into rivers and lakes, and waste from intensively managed livestock farms (2,8). Several studies have proven that the bacterial genotypes found in wildlife in terms of sequence types and clinically relevant antibiotic resistance determinants resemble those found in humans and animals (10). Other reports found only a limited overlap in this regard, indicating that the horizontal transfer of genes via mobile genetic elements might play a more central role (11).…”
mentioning
confidence: 99%